Enterprise Resource Planning Systems (2000–2026): Scopus-Based Bibliometric Mapping of Knowledge Domains and Influential Studies - Judijanto, Loso (Westscience Press, 2026)
This research paper seeks to examine the development and structure of knowledge in the field of ERP research from 2000 to 2026 employing bibliometrics as a methodological tool. To achieve this purpose, the data were gathered from the Scopus database and analyzed via VOSviewer to visualize co-authorship patterns, citations, and co-occurrences of keywords. According to the findings, the subject area of ERP research has expanded from initial issues concerning implementation to more sophisticated themes, which are associated with digital transformation, such as artificial intelligence, cloud computing, and big data analytics. The co-authorship network shows the dispersed collaboration among authors, even though there is dominance among a few countries, including China, the United States, and India, in producing global knowledge. Citation analysis demonstrates the interdisciplinarity of ERP research, considering various lenses such as information systems, organizational theory, and emerging digital technologies. On the other hand, the keyword analysis illustrates a transition from problems relating to operations and management to those regarding strategies and technologies. In summary, this research paper will make a valuable contribution to future literature by providing an overall picture of ERP research in terms of its evolution, key figures, and trends.